Inactivation of glucocorticoid receptor in noradrenergic system influences anxiety- and depressive-like behavior in mice - Chmielarz, Piotr; Kuśmierczyk, Justyna; Parlato, Rosanna; Schütz, Günther; Nalepa, Irena; Kreiner, Grzegorz (PLOS ONE, 2013)
The aim of this study was to investigate whether conditional inactivation of the glucocorticoid receptors (GRs) in noradrenergic neurons affects animal behavior in mice. Selective ablation of GRs in the noradrenergic system was achieved using the Cre/loxP approach. We crossed transgenic mice expressing the Cre recombinase under the dopamine beta-hydroxylase (DBH) promoter with animals harboring the floxed GR gene. The resulting GRDBHCre mutant mice exhibited no alterations in terms of normal cage behavior, weight gain, spatial memory or spontaneous locomotor activity, regardless of gender. To assess depressive- and anxiety-like behaviors we performed the Tail Suspension Test and the Light-Dark Box Test. While male mutant animals did not show any alternations in both tests, female GRDBHCre mutants displayed depressive- and anxiety-like behavior. Additionally, male GRDBHCre mice were exposed to chronic restraint stress but still exhibited immobility times and anxiety statuses similar to those of non-stressed animals while stressed control mice clearly revealed depressive- and anxiety-like phenotype. Thus, in males the effects of the mutation were precipitated only after chronic restraint stress procedure. Our data reveal a possible gender-dependent role of GRs in the noradrenergic system in anxiety- and depressive-like behavior in mice.
Gesehen am 14.04.2021